Location of R&D and high-tech production by vertically integrated multinationals - Karolina Ekholm; Katariina Hakkala (Stockholm School of Economics, The Economic Research Institute (EFI), 2003)
We develop a two-country general equilibrium model where firms make separate choices about the location of R&D and high-tech production. There are two agglomeration forces: R&D spillovers and backward linkages associated with high-tech production. The latter tends to attract production to the larger economy. We show that, for relatively weak R&D spillovers and intermediate trade costs, the smaller economy tends to specialize in R&D. For certain parameterizations, both concentration and dispersion of R&D activities are possible outcomes. Hosting an agglomeration of R&D activities does not necessarily lead to welfare gains.
Keywords: F12; F23; 330; monopolistic competition; R&D; high-tech production; agglomeration economies; Monopolistischer Wettbewerb; Hochtechnologiesektor; Agglomerationseffekt; Industrielle Forschung